G99(P) Respiratory support for infants with bronchiolitis in a High Dependency Unit of a UK children's hospital. (7th April 2014) - Sinha, IP; Syahanee, R; Piper, JD; Halfhide, C; Mayell, SJ
Abstract : Aims: Results from observational studies in infants with severe bronchiolitis suggest that nasal Continuous Positive Airway Pressure (nCPAP) and High Flow Nasal Cannulae Oxygen (HFNC) may improve physiological parameters and reduce respiratory distress. We aimed to examine trends in the use of headbox oxygen, CPAP and HFNC, in infants with bronchiolitis, admitted to our regional children's hospital High Dependency Unit (HDU). Method: We retrospectively reviewed electronic case records of infants aged less than one year, with a clinical diagnosis of bronchiolitis admitted to HDU between 2003 and 2013. We collected data on: age of admission, RSV-status, first modality of respiratory support used, whether the infant was transferred to Paediatric Intensive Care Unit (PICU), and length of HDU stay. In our hospital, CPAP and HFNC are only used on HDU or PICU. We excluded infants who were already in-patients with other problems and those transferred to HDU from other hospitals or after ventilation on PICU. Results: Over the 10 consecutive seasons, 138 eligible infants with bronchiolitis were admitted to HDU, median age 1.5 [IQR 1, 3] months; RSV was isolated in 112/138 (81%). 18/138 (13%) required subsequent admission to PICU. Trends in the use of headbox oxygen, nCPAP, HFNC, and admission rates from HDU to PICU, are shown in Figure 1 . Median length of stay on HDU increased from two to four days (see Figure 1 ). Conclusion: We observed a change in the initial modality used to support infants with severe bronchiolitis on HDU from headbox oxygen, to nCPAP and HFNC. During the study period there was an initial increase in admission rates to PICU which reversed after 2006. The use of nCPAP and HFNC seemed to increase the length of stay on HDU, and we are developing decision aids to help wean infants from these therapies appropriately. Our study, which covers a longer timeframe and includes more infants than other UK studies, supports the use of CPAP and HFNC, for infants with severe bronchiolitis in a HDU setting.